Flyway‐scale analysis reveals that the timing of migration in wading birds is becoming later. Issue 20 (28th September 2021) - Mondain‐Monval, Thomas O.; Amos, Matt; Chapman, Jamie‐Leigh; MacColl, Andrew; Sharp, Stuart P.
Abstract: Understanding the implications of climate change for migratory animals is paramount for establishing how best to conserve them. A large body of evidence suggests that birds are migrating earlier in response to rising temperatures, but many studies focus on single populations of model species. Migratory patterns at large spatial scales may differ from those occurring in single populations, for example because of individuals dispersing outside of study areas. Furthermore, understanding phenological trends across species is vital because we need a holistic understanding of how climate change affects wildlife, especially as rates of temperature change vary globally. The life cycles of migratory wading birds cover vast latitudinal gradients, making them particularly susceptible to climate change and, therefore, ideal model organisms for understanding its effects. Here, we implement a novel application of changepoint detection analysis to investigate changes in the timing of migration in waders at a flyway scale using a thirteen‐year citizen science dataset (eBird) and determine the influence of changes in weather conditions on large‐scale migratory patterns. In contrast to most previous research, our results suggest that migration is getting later in both spring and autumn. We show that rates of change were faster in spring than autumn in both the Afro‐Palearctic and Nearctic flyways, but that weather conditions in autumn, not in spring, predicted temporal changes in the corresponding season. Birds migrated earlier in autumn when temperatures increased rapidly, and later with increasing headwinds. One possible explanation for our results is that migration is becoming later due to northward range shifts, which means that a higher proportion of birds travel greater distances and therefore take longer to reach their destinations. Our findings underline the importance of considering spatial scale when investigating changes in the phenology of migratory bird species. Abstract : Millions of birds migrate annually providing valuable ecosystem services, but we know little about macroecological changes occurring due to climate change. Our results suggest that continental‐scale wading bird migration has become later over the last decade, contrary to many studies at the population‐level, suggesting that changes in the timing of bird migration might differ across spatial scales. More work is urgently needed to investigate large‐scale patterns in the phenology of migratory animals.